Urban boundary layer wind speed reduction in summer due to urban growth and environmental consequences in Lisbon - Lopes, António (2019)
Knowledge of the mesoscale wind systems is very important to understand the dispersion of pollutants, thermal regulation and human comfort in the city. Wind field modifications brought about by the growth of the city of Lisbon and the possible urban environmental impacts are presented. In the last years the city of Lisbon has been growing towards the northern districts and the city center looses an efficient way to remove pollutants and effective way to control thermal comfort because of the consequent reduction in the wind speed average. It was concluded that until the eighties of the 20th century, there was a 30% reduction of the surface summer wind speed over Lisbon and that in the near future the increase of the aerodynamic roughness (z0) from 0.02 m to 1.5 m windward of the city will cause a 40% reduction of the wind speed above the buildings. This information can be very important to help urban planners to plan ventilation paths for the prevailing north winds towards the city center.